2016
DOI: 10.1007/s00384-016-2580-z
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial comparing water exchange and air insufflation during colonoscopy without sedation

Abstract: WE is superior to AI for attenuating insertion pain during colonoscopy without sedation, but its efficacy is limited in more painful endoscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
1
18
0
Order By: Relevance
“…Adenoma detection rate was described in 16 studies. 17,18,23,24,27,31,33,34,38,40,41,45,46,49,52,55 We observed that air insufflation (OR = 0.71, 95% CrI: 0.6-0.83, Table 3), CO 2 insufflation (OR = 0.75, 95% CrI: 0.56-0.99, Table 3) and water immersion (OR = 0.77, 95% CrI: 0.62-0.96, Table 3) had a significantly lower adenoma detection rate than water exchange.…”
Section: Adenoma Detection Ratementioning
confidence: 78%
See 3 more Smart Citations
“…Adenoma detection rate was described in 16 studies. 17,18,23,24,27,31,33,34,38,40,41,45,46,49,52,55 We observed that air insufflation (OR = 0.71, 95% CrI: 0.6-0.83, Table 3), CO 2 insufflation (OR = 0.75, 95% CrI: 0.56-0.99, Table 3) and water immersion (OR = 0.77, 95% CrI: 0.62-0.96, Table 3) had a significantly lower adenoma detection rate than water exchange.…”
Section: Adenoma Detection Ratementioning
confidence: 78%
“…Forty RCT with 13 734 patients were included from 1060 articles searched through databases and other sources (Fig. ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our search identified 155 publications. Seventeen RCTs [2][3][4][5][6][9][10][11][17][18][19][20][21][33][34][35][36] were included in the analysis (41 arms of treatment, 10,350 patients; 55.7% male patients; Supplementary Figs. 1 and 2, available online at www.…”
Section: Resultsmentioning
confidence: 99%